Effect of alkali treatments on physical and mechanical strength of pineapple leaf fibres - Khan, Mohammad Asim; Jawaid, Mohammad; Abdan, Khalina; Mohamed Nasir (IOP Publishing, 2018)
Pineapple leaf fibre (PALF) is a waste material of pineapple plants. PALF is abundant in amount for industrial purpose, cheap, easily available, high specific strength and stiffness. PALF is contributing a sustainable development in bio-composites as reinforcement material. However, natural fibres are not fully compatible with matrix due to hydrophilic in nature. To enhance the compatibility with matrix, fibres are modified its surface to make good interfacial bonding with matrix. In this research, PALF is treated with 3% and 6% concentration of NaOH for 3h, 6h 9h, and 12h soaking time. Surface modification of fibres was investigated by using scanning electron microscopy. Single fibre test and diameter of PALF fibres were evaluated the effects of NaOH treatments.